Age, Onset, and Tumor Size Differences in Newly Diagnosed Breast Cancer Patients Before and During the SARS-CoV-2 Pandemic at Siloam Hospital Lippo Village (April 2019 - December 2020) - Halim, Freda Susana (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: The current pandemic condition has caused delays in cancer treatment therefore surveillance should be increased.Methods: By total sampling, this retrospective cross-sectional study enrolled 108 samples, who were newly diagnosed breast cancer patients at the outpatient department of Siloam Hospital Lippo Village (April 2019 - December 2020). Data obtained from medical records and interviews from December 2020 - February 2021.Result: From the total of 108 samples which consisted of 54 samples before the pandemic (April 2019 - February 2020) and 54 samples during the pandemic (March 2020 - December 2020), accompanied by an increasing trend. The age during pandemic was younger than before pandemic (51,167 years old ± 11,255 vs 47,537 years old ± 9,824, p value=0,038), the tumor size during pandemic was bigger than before pandemic (3,403 cm ± 3,024 vs 4,262cm ± 4,212, p value=0,046) but the onset of patient during pandemic was not longer than before pandemic (281,69 days ± 401,387 vs 178,09 days ± 292,563, p value=0,036).Conclusions: Newly diagnosed patients have younger age and larger tumor size during pandemic when we compare to before pandemic period, but no difference in onset term. Surveillance to society is needed to ensure older people with smaller tumor size to seek medical attention.